Identifying and Handling Implementation Challenges of Self-Service Business Intelligence - Qudaisat, Sameer Yousef; Al Talafheh, Khairallah Mohd (Journal of Ecohumanism, 2024)
Self-service has recently become a defining feature of business intelligence (BI) and analytics platforms. Self-service Business Intelligence (SSBI) enables business users to generate reports and analysis of business data without the intervention of IT department. It responds to a need to quickly create reports and analysis to make business-critical decisions. However, introducing SSBI poses implementation challenges, and many of the companies that have introduced it became dissatisfied with the implementation results. The purpose of the study is to create an understanding of how challenges related to SSBI implementation are handled for enabling a successful implementation. This leads to the question: How the challenges related to SSBI implementations are handled? To answer the question, six interviews were conducted at an anonymous company with respondents who in various ways have a connection to the introduction of SSBI. The result of the study is a model of the user-related challenges of introducing SSBI and the recommendations identified in this work for how they can be managed. By using these challenges when introducing SSBI, businesses can provide users with good conditions, which increases the possibility of introducing a successful and sustainable SSBI.